Factors associated with having a medical marijuana card among Veterans with recent substance use in VA outpatient treatment. (December 2016) - Davis, Alan K.; Bonar, Erin E.; Ilgen, Mark A.; Walton, Maureen A.; Perron, Brian E.; Chermack, Stephen T.
Abstract: Psychiatric symptoms, somatic problems, and co-occurring substance use have been associated with medical marijuana consumption among civilian patients with substance use disorders. It is possible that these factors may impact Veterans' ability to engage in or adhere to mental health and substance use disorder treatment. Therefore, we examined whether psychiatric functioning, substance use, and somatic problems were associated with medical marijuana use among Veterans receiving substance use disorder and/or mental health treatment. Participants (n = 841) completed screening measures for a randomized controlled trial and 67 (8%) reported that they had a current medical marijuana card. Most of these participants (78%) reported using marijuana to treat severe/chronic pain. Significant bivariate differences revealed that, compared to participants without a medical marijuana card, those with a card were more likely to be in a middle income bracket, unemployed, and they had a significantly higher number of recent days of marijuana use, synthetic marijuana use, and using sedatives prescribed to them. Additionally, a significantly higher proportion of participants with a medical marijuana card scored above the clinical cutoff for posttraumatic stress disorder (PTSD) symptoms, had significantly higher severity of sleep-related problems, and reported a higher level of pain. These findings highlight the co-occurrence of substance use, PTSD symptoms, sleep-related problems, and chronic pain among Veterans who use medical marijuana. Future research should investigate the inter-relationships among medical marijuana use and other clinical issues (e.g., PTSD symptoms, sleep, pain) over time, and potential implications of medical marijuana use on treatment engagement and response. Highlights: Among Veterans with a medical marijuana card, most report using it for chronic pain PTSD, sleep problems, and pain level are associated with having a medical marijuana card Assessing medical marijuana use may be important among Veterans in SUD treatment